In silicio Identification of Glycosyl-Phosphatidylinositol-Anchored Plasma-Membrane and Cell Wall Proteins of Saccharomyces cerevisiae - Heleen, L.; Caro, P.; Tettelin, H.; Vossen, J.H.; Ram, A.F.J.; Van Den Ende, H.; Klis, F.M.
Use of the Von Heijne algorithm allowed the identification of 686 open reading frames (ORFs)in the genome of Saccharomyces cerevisiae that encode proteins with a potential N-terminal signal sequence for entering the secretory pathway. On further analysis, 51 of these proteins contain a potential glycosyl-phosphatidylinositol (GPI)- attachment signal. Seven additional ORFs were found to belong to this group. Upon examination of the possible GPI-attachment sites, it was found that in yeast the most probable amino acids for GPI-attachment are asparagine and glycine. In yeast, GPI-proteins are found at the cell surface, either attached to the plasma-membrane or as an intrinsic part of the cell wall. It was noted that plasma-membrane GPI-proteins possess a dibasic residue motif just before their predicted GPI-attachment site. Based on this, and on homologies between proteins, families of plasma-membrane and cell wall proteins were assigned, revealing 20 potential plasma-membrane and 38 potential cell wall proteins. For members of three plasma-membrane protein families, a function has been described. On the other hand, most of the cell wall proteins seem to be structural components of the wall, responsive to different growth conditions. The GPI-attachment site of yeast slightly differs from mammalian cells. This might be of use in the development of anti-fungal drugs.
Keywords: GPI-ANCHOR; GPI-ATTACHMENT SITE; YEAST; ASCOMYCETES; FUNGI